Unified description of bifurcation processes associated with laminar boundary‐layer separation. Issue 1 (21st October 2015) - Kluwick, Alfred; Braun, Stefan
Abstract: The presentation will concentrate on flows where no steady state exists if an appropriately defined controlling parameter exceeds a critical value while non‐uniqueness is observed for sub‐critical values of this parameter. Special attention is placed on flow phenomena which are associated with the passage through criticality. Based on a triple deck analysis it found that they can be described as solutions of differential equations of Fisher type which are better known from evolution studies of gene populations. Special examples which will be discussed include 2D marginally separated flows, weakly 3D transonic flows in slender channels and fully 3D subsonic flow past expansion ramps. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)